Lake Fryxell 2022-2023 benthic microbial mat thickness and number of laminae ... - Juarez Rivera, Marisol; Mackey, Tyler; Paul, Ann; Hawes, Ian; Sumner, Dawn (U.S. Antarctic Program (USAP) Data Center, 2024)
This dataset contains measurements of microbial mat thickness and number of laminae from Lake Fryxell, McMurdo Dry Valleys, Antarctica. Holes were melted through the ice cover of Lake Fryxell, which allowed tethered divers to collect benthic microbial mats (non-liftoff and liftoff) and microbial mats at the ice-water interface (float mats). Benthic non-liftoff and liftoff mat samples were collected from 4.3 m (n=4), 6.1 m (n=4), and 7.9 m (n=4) depths. Float mats were collected from the ice-water interface above 4.3 m (n=4), 6.1 m (n=4), and 7.9 m (n=5) depths. The mats were dissected along vertical cross sections in the field to measure mat thickness and number of laminae. Additional funding for this work was provided by the NASA Solar System Workings Program (Award #80NSSC22K0709). ...